2020
DOI: 10.3390/molecules25184287
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Traditional and Non-Thermal Treatments on the Bioactive Compounds and Sugars Content of Red Bell Pepper

Abstract: The aim of the study was an investigation of the effect of traditional and non-thermal treatment on the bioactive compounds of red bell pepper. As a thermal process, blanching in water and in steam was studied, while for non-thermal the sonication, pulsed electric field treatment and their combination were used in this experiment. The red bell peppers were evaluated based on quality attributes such as: total carotenoids content; polyphenols; vitamin C; antioxidant activity and sugars content. Vitamin C and sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 63 publications
3
26
0
Order By: Relevance
“…Such results can be associated with the dimensions of ice crystals that are formed during vacuum freezing in comparison to shock freezing. It has been reported that vacuum-induced freezing results in the formation of chimney-like big ice crystals, which can rupture the cellular structure even more and thus improve the extractability of sugars [ 52 , 53 ]. Such explanation sounds reliable when comparing the results obtained for the samples treated using the same pretreatment conditions but different drying methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such results can be associated with the dimensions of ice crystals that are formed during vacuum freezing in comparison to shock freezing. It has been reported that vacuum-induced freezing results in the formation of chimney-like big ice crystals, which can rupture the cellular structure even more and thus improve the extractability of sugars [ 52 , 53 ]. Such explanation sounds reliable when comparing the results obtained for the samples treated using the same pretreatment conditions but different drying methods.…”
Section: Resultsmentioning
confidence: 99%
“…It can be stated that the sequence of the hybrid treatment and freezing method is important in the case of bioactive compounds. As previously mentioned, the combination of novel treatment as PEF and US may be associated with different mechanisms connected to the influence of enzymes, structural changes, better extractability, and color changes [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The blanching process results in a lighter color due to the leaching of the coloring components into the surrounding water. The blanching process causes the reduction of carotenoids [45], which gives the red color for bell pepper. During the blanching process the water caused damages to the tissue [46], which facilitated the leaching of the color pigments.…”
Section: Color Parameters Of Freeze-dried Red Bell Peppermentioning
confidence: 99%
“…This complex has a higher polarity and flows more easily into the surrounding water during PEF treatment. On the other hand, PEF treatment, as well as US treatment, may generate free radicals, which affect the carotenoids [45] and thus the color. Conversely, the combinations of treatments applied prior to drying also affect the color of the red pepper.…”
Section: Color Parameters Of Freeze-dried Red Bell Peppermentioning
confidence: 99%
“…This decrease in vitamin C content is due to pre-treatment (blanching) and drying. Some studies [4], [5], [9], [10], [26]explained that several factors caused the decrease of vitamin C content, i.e., 1) vitamin C is water-soluble, therefore the washing and blanching process can decrease the vitamin C content, and 2) vitamin C is easy to be damaged due to heat. During blanching, the heating process causes oxidation of vitamin C. Heating the chilies twice, i.e., when blanching for 10 minutes at 90°C using metal heaters and drying, it causes an oxidation process.…”
Section: Vitamin C Contentmentioning
confidence: 99%